Mechanical characterization of visually graded boards from turkish fir and black pine by nondestructive and destructive tests - Kurul, Fatih; Şişman, Ömer Asım; Dündar, Türker (Maderas. Ciencia y Tecnología, 2023)
For the mechanical characterization of Turkish fir and black pine, 400 board specimens with 22 mm× 50 mm × 420 mm were visually graded according to TS 1265 standard. Nondestructive tests were here upon performed using the stress wave method. After specimens were intentionally tested under flatwise bending to research the applicability as an alternative to tension and edgewise bending tests in European strength grading system. According to analyses of variance, the mean values of MOR and MOE differed in four groups at a p<0,05 significance level for visually graded boards. High correlations were found between MOR-MOE (R2=0,837) for fir and MOR-MOE (R2=0,776) for black pine. In addition, correlations of MOR-Knot rate for fir and black pine were respectively R2=0,669 and R2=0,660 showing the effectiveness of flatwise bending tests with the visual grading standard. For nondestructive tests, the mean values of the dynamic modulus of elastici- ty were very close in between fir and black pine grades while the usage of defect-free density performed better than the density of the whole specimen. Higher strength classes were found for black pine boards (Class 1= C40, Class 2= C27 and Class 3= C22) compared to fir boards (Class 1= C24, Class 2= C22 and Class 3= C18), respectively. Moreover, a simplified nonlinear material model was proposed for numerical modelling, and the results were found in good agreement in terms of the bending stiffness, strength, and deformation capacity of boards especially for class 1 and class 2 in both softwood species.